Creating a model of diffusion deposition of metal coatings from melts of low-melting metals - Sivenkov, A V; Nikitina, V O; Serdiuk, N A; Konchus, D A; Pryakhin, E I (IOP conference series. Materials Science and Engineering, 2019)
The object of the research is to apply a diffusion layer of nickel from a liquid lead melt, and the subject is the optimal interaction of factors that influence the creation and growth of a diffusion layer. In this paper, the main factors affecting the rate of formation of the nickel coating are analyzed, the effective diffusion coefficients of nickel coatings are calculated for the 1.0036 and 1.0503 steels, and the activation energy for diffusion is determined. Based on the data obtained, empirical formulas are obtained for determining the thickness of the diffusion layer as a function of temperature and saturation time of the process.